Report of three centrohelid heliozoan species (Centroplasthelida Febre-Chevalier et Febre) from new localities in Europe with notes on their distribution - Gaponova, Liudmyla; Suzaki, Toshinobu (Zootaxa, 2024)
Raphidocystis marginata (Siemensma, 1981), Raineriophrys echinata (Rainer, 1968), and Pterocystis fortesca (Nicholls, 1983) are heliozoan protists, have been recorded only in a few localities in Europe, and considered to be rare species. These centrohelid heliozoans have been reported for the first time in Ukrainian Polissia, and we provide their morphological descriptions with new morphometric data of exoskeleton (periplast) based on Ukrainian material. The diagnostic morphological characters are illustrated by light and scanning electron microscope photographs. Their geographical distribution in Europe and biotope preference are discussed.